Tick-borne viruses: Epidemiology, pathogenesis, and animal models - Kwang-Min Yu; Su-Jin Park (One Health)
Tick-borne viruses, capable of infecting animals and humans, are expanding geographically and increasing in prevalence, posing significant global public health threats. This review explores the current epidemiology of human pathogenic tick-borne viruses, emphasizing their diversity and the spectrum of symptomatic manifestations in humans, which range from mild to severe. We highlight how the infrequent and unpredictable nature of viral outbreaks complicates the precise identification and understanding of these viruses in human infections. Furthermore, we describe the utility of animal models that accurately mimic human clinical symptoms, facilitating the development of effective control strategies. Our comprehensive analysis provides crucial insights into disease progression and emphasizes the urgent need for continued research. This work aims to provide insight into knowledge gaps to mitigate the health burden of tick-borne infections and open an avenue for further study to enhance our understanding of these emerging infectious diseases.